Medicinal Importance, Pharmacological Activities, and Analytical Aspects of Engeletin in Medicine: Therapeutic Benefit Through Scientific Data Analysis - Patel, Dinesh K. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Phytochemicals belonging to the class of flavonoids have been used in medicine for the treatment of different kinds of human health complications. Flavonoids have beneficial health aspects in medicine mainly due to their anti-microbial, anti-diabetic, anti-inflammatory, anticancer, and anti-carcinogenic activities. They have been scientifically investigated for their health benefit and pharmacological activities in medicine. Engeletin is a pure flavanonol class phytocompound present in the skin of white grapes and white wine. Engeletin has numerous pharmacological activities in medicine. Methods: In order to know the beneficial health aspects of engeletin in medicine, scientific data on engeletin have been collected from different literature sources and analyzed in the present work. The present work summarized the important findings of engeletin with respect to its medicinal uses, pharmacological activities, and analytical aspects in medicine. All the scientific data were collected from PubMed, Google, Scopus, Science Direct and Google Scholar and analyzed in the present work. Results: Scientific data analysis of research works revealed the biological importance and therapeutic benefit of engeletin in medicine. Engeletin has attracted scientific attention mainly due to its antiinflammatory and anti-tumor potential. Engeletin could inhibit the occurrence of cervical cancer and delay the development of liver damage and lung cancer in mice. Engeletin was found to inhibit lipopolysaccharides- induced endometritis in mice by inhibiting the inflammatory response. Pharmacological data analysis revealed the therapeutic importance of engeletin against acute lung injury, inflammatory diseases, liver injury, pulmonary fibrogenesis, Alzheimer’s disease, endometritis, cervical carcinogenesis, lung cancer, and osteoarthritis. Analytical data signified the importance of modern analytical tools for separating, isolating, and identifying engeletin. Conclusion: Scientific data analysis revealed the biological importance and therapeutic benefit of engeletin in medicine and other allied health sectors.
Keywords: endometritis